Analysis of mucociliar transport in ceramic workers: a cross-sectional study (Research, Society and Development, 2022)
Brazil is the fourth largest producer of ceramic products in the world, and the large amount of raw material and technological evolution are the main responsible for the advancement of industries in the country. The inhalation of dust and smoke particles can be deposited in the airways, and interfere with the defense mechanisms of these and the lung, contributing to the development of multiple diseases of the respiratory system. To keep itself clean and healthy, the respiratory tract has an effective defense mechanism: “mucociliary transport”. The work performed in ceramic industries is among the human activities capable of altering it. Several methods allow the analysis of mucociliary transport, one of which is the saccharin transit time (TTS) test. This study aims to evaluate nasal mucociliary transportability in ceramic workers in the Pontal do Paranapanema region. Refers to an analytical, cross-sectional study with a quantitative approach. Workers from ceramic industries specializing in the manufacture of bricks. An electronic database will be created for the analysis of the results. The values ​​will be tested by the normality of Kolmogorov-Smirnov and in case of parametric normal distribution, the ANOVA analysis of variance will be performed. The Kruskal-Wallis test will be used for cases of non-norm and non-parametric distribution, with significant values ​​referring to p